Selfie and Narcissism in Young Adults - Bhachech, Jyotik Tarak (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2021)
Selfie, a commonly observed behaviour, is symbol of virtual identity. Similarly, narcissism as described by grandiose view of oneself, seeking approval and admiration on social media is also frequent. The purpose of this study is exploring selfie taking behaviour and narcissism among young adults. A total 132 subjects were considered for study through an online questionnaire which included demographic variables, selfie taking behaviour and NPI-16 (Narcissistic Personality Inventory -16). The results showed majority of the subjects N = 76 (57.5%) had high narcissism (NPI â‰¥ 7). Age group 15 to 25 years (p= 0.0200), males, subjects who stayed in city, post graduates or graduate qualification, and married subjects had high narcissism. Using smart phone use more than 5 years (p=0.00942), taking 5 to 10 selfies per day with (p=0.00331), posting selfie for personal memory (p=0.03268), selfie on WhatsApp messenger (p=0.03268) and taking selfie with person alone and selfie taken on specific occasions (p=0.01122), had high narcissism. The conclusion of this study is selfie and narcissism are closely linked among young adults and a matter of psychological wellbeing during personality development.